Physiological and metabolic responses to constant and variable load cycling performance - Palmer, Gary Stanley (MRC/UCT RU for Exercise and Sport Medicine, 2018)
The experiments described in this thesis comprise a series of related, yet independent investigations examining the physiological and metabolic responses of well-trained amateur cyclists under conditions designed to mimic actual competitive situations, during individual and mass start races. In Section A the physiological responses to constant load and steady state exercise are determined. In Section B, the metabolic factors associated with constant and variable load cycling performance are examined.